Influencing factors in choosing delivery method: Iranian primiparous women’s perspective - Moosavi, Ahmad (Electron Physician, 2017)
BACKGROUND: Studies on the primiparous mothers’ decision on delivery method are limited. AIM: The aim of his study was to determine the factors that influence the choice of delivery method by Iranian primiparous women. METHODS: This cross-sectional study was conducted in April through September 2014. Participants were 460 primiparous women in 8 hospitals of 4 cities in Iran. Finally, 230 cesarean section and 230 vaginal delivery women were selected. Inclusion criteria were being primiparous, and having no contraindication for vaginal delivery. Study tool was a researcher-developed questionnaire that its validity and reliability were proved. Data were gathered by direct interview and analyzed by SPSS version 16. RESULTS: Average age of the participants was 23 years. Factors that correlated with the choice of Cesarean section were upper education, high socioeconomic level, tendency of husband, living with the husband’s family, insistence of the physician, receiving maternal care in personal offices, fear of delivery pain, low knowledge of the mother, high age of marriage and pregnancy, history of abortion, and lack of family support. More than 60% of the participants had little knowledge about the delivery methods. Satisfaction with cesarean section was 70% and with the vaginal delivery was 77%. Half of the cesareans were performed on the insistence of the physician. CONCLUSION: Considering the factors identified in this study, can enforce the intention of mothers to have vaginal delivery by improving their knowledge and perception about this delivery method.